SOURCE AND TARGET LANGUAGE ORIENTED ON THE BICYCLE RIDER BY TOM W. SHAPCOTT ON SAPARDI DJOKO DAMONO’S TRANSLATION (A CASE STUDY) - Eka Ugi Sutikno; Praksi - Kurniawan; Onny Bisma Dwi Nugroho; Nina - Alfah; Erien Rida Winarti; Vinanda - Audria; Kamelia - - (Globish: An English-Indonesian Journal for English, Education, and Culture, 2022)
The cultural differences between English and Indonesian languages impact the language used if vice versa, translations should suffice. The translation is a result of the distinctions outlined. This article aims to analyze the source and target Language oriented on The Bicycle Rider by Tom W. Shapcott on Sapardi Djoko Damono’s Translation. This approach is structured based on the topic matter and the study’s primary purpose. Data collection, analysis, and research design are part of this study’s methodology. To analyze The Bicycle Rider by Tom W. Shapcott on Sapardi Djoko Damono’s translation, we use Newmark’s theory as the base thinking. In this translation, we found six free translation methods, five semantic translation methods, five literal translation methods, and two adaptation translation methods. The conclusion is that this translation has dominated by source language-oriented translation; meanwhile, it has some target language-oriented translation.